Eco-friendly and economically optimal design model (EEODM) to reduce the CO2 emissions and the cost of long-span waffle slabs. (10th May 2021) - Lee, Seung Hyeong; Oh, Byung Kwan; Choi, Jewoo; Hong, Do Hun; Hong, Taehoon; Lee, Dong-Eun; Park, Hyo Seon
Abstract: As the emission of CO2 is directly proportional to the nature of the materials used in the construction of buildings, an eco-friendly economic design is required for waffle slabs used in large buildings such as stores, shopping malls. In this study, a multi-objective optimization design model, denoted as an eco-friendly and economically optimal design model (EEODM), is proposed to reduce the CO2 emissions and costs of long-span waffle slabs. The developed model was analyzed to determine the change in CO2 emissions and costs with respect to design variables in 20 types of long-span waffle slabs. Based on the results of the analysis, CO2 emission efficiency analysis (CEEA) and cost-efficiency analysis (CEA) are proposed as the new qualitative scales to determine environmental and economic feasibility, respectively. Through CEEA and CEA, a new design standard is proposed to overcome the limitations of existing waffle forms. To verify the applicability of the EEODM, the model proposed in this study was applied to the actual waffle slab of Gimpo International Airport in Korea. The results indicate that the two proposed waffle forms reduced CO2 emissions and costs compared to the existing sections of the airport. Highlights: Eco-friendly and economically optimal design model (EEODM) for long-span waffle slabs is proposed. New quantitative measures of eco-friendliness and cost were defined by CEEA and CEA. New waffle slab design standards that can be used in various construction environments were proposed. The proposed two waffle forms reduced both emissions and cost compared to the existing sections of Gimpo Airport.